VALIDASI METODE PENENTUAN ARSENIK PADA SAMPEL AIR SUMUR BOR DENGAN MENGGUNAKAN SPEKTROFOTOMETER SERAPAN ATOM DI PT. GEOSERVICES BALIKPAPAN - Bayu Iskandar; Aman Sentosa Panggabean; Rudi Kartika (PROSIDING SEMINAR KIMIA, 2017)
Research on the validation of As determination methods on wellbore water by using atomic absorption spectrophotometer at PT. Geoservices Balikpapan has been calculated. The validation method used is APHA-3114 C, with research stages such as linearity, detection limit, quantitative limit, accuracy, precision. The results showed that the linearity test had good result with R2 ≥ 0.9997. The detection limit value was 0,000038 µg/Land the quantization limit value was 0,00129 µg/L. The %KV value obtained is smaller than the 2/3 KVHorwitz value, indicating that this method has a good precision. The determination of As in drilled well water samples is 0.9167 µg/L, then below the standard threshold of clean water quality quality based on Permenkes. 416/Menkes/PER/IX/1990. Based on the results of the research, APHA-3114 B/C method can be used to determine As in drilled well water samples. Keywords: Validation method, arsenic, wellbore water, APHA-3114B/C, AAS-VHGA.